2023
DOI: 10.1590/1516-3180.2022.0226.r1.21072022
|View full text |Cite
|
Sign up to set email alerts
|

Association between multimorbidity, intensive care unit admission, and death in patients with COVID-19 in Brazil: a cross-section study, 2020

Abstract: BACKGROUND: Multimorbidity can influence intensive care unit (ICU) admissions and deaths due to coronavirus disease . OBJECTIVE: To analyze the association between multimorbidity, ICU admissions, and deaths due to COVID-19 in Brazil. DESIGN AND SETTING: This cross-sectional study was conducted using data from patients with severe acute respiratory syndrome (SARS) due to COVID-19 recorded in the Influenza Epidemiological Surveillance Information System (SIVEP-Gripe) in 2020. METHODS: Descriptive and stratified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(29 reference statements)
1
3
0
1
Order By: Relevance
“…They also consider earlier waves of the pandemic (study period between January 2020 and July 2021) and address short-term outcomes, notably in terms of infection, hospitalisation, ICU admission and mortality. The studies support our findings underlying the higher risk of poorer outcomes with the higher number of diseases or with a CCI score increment [ 55 , 56 , 58 , 59 , 61 , 62 ], with increasing frailty [ 63 65 ] and for certain disease patterns such as cardiometabolic or cardiovascular patterns, which presented a stronger association with infection or infection severity [ 57 , 60 ]. Regarding the risk of infection, however, the findings seem to be less conclusive, for e.g., Catalano et al [ 58 ] showed the lesser likelihood of infection for patients with multimorbidity, even though they were tested more often, which may potentially be explained by their better compliance with the restrictive measures; nevertheless, in the same study, the risk of hospitalisation, ICU admission or death was higher for patients with multimorbidity.…”
Section: Discussionsupporting
confidence: 84%
“…They also consider earlier waves of the pandemic (study period between January 2020 and July 2021) and address short-term outcomes, notably in terms of infection, hospitalisation, ICU admission and mortality. The studies support our findings underlying the higher risk of poorer outcomes with the higher number of diseases or with a CCI score increment [ 55 , 56 , 58 , 59 , 61 , 62 ], with increasing frailty [ 63 65 ] and for certain disease patterns such as cardiometabolic or cardiovascular patterns, which presented a stronger association with infection or infection severity [ 57 , 60 ]. Regarding the risk of infection, however, the findings seem to be less conclusive, for e.g., Catalano et al [ 58 ] showed the lesser likelihood of infection for patients with multimorbidity, even though they were tested more often, which may potentially be explained by their better compliance with the restrictive measures; nevertheless, in the same study, the risk of hospitalisation, ICU admission or death was higher for patients with multimorbidity.…”
Section: Discussionsupporting
confidence: 84%
“…T h e i n d e p e n d e n t v a r i a b l e w a s multimorbidity, measured by counting selfreported morbidities in response to the question "Has a doctor told you that you have...? ", based on a list of 12 Multimorbidity was operationalized as an ordinal variable, classified into three categories: zero to one morbidity; two morbidities; three or more morbidities. 17,18 The following variables were used as independent covariables: a) sex (male; female); b) aged (in years: 18…”
Section: Original Articlementioning
confidence: 99%
“… 10 Around 72% of individuals in intensive care units (ICUs) had multimorbidity, 11 and prevalence of admissions to and deaths in ICUs grew as the number of morbidities increased. 12 Multimorbidity, therefore, affects health service use indicators, such as hospitalizations and simultaneous use of several services at different levels of care. 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Cerca de 72% dos indivíduos das unidades de terapia intensiva (UTIs) apresentavam multimorbidade, 11 e a prevalência de internações e óbitos em UTIs crescia à medida que aumentava o número de morbidades. 12 A multimorbidade, portanto, afeta os indicadores de utilização dos serviços de saúde, como internações e uso simultâneo de vários serviços nos diferentes níveis da atenção. 13 A literatura mais atual mostra que indivíduos com multimorbidade utilizam mais os serviços de saúde, 13,14 embora dados sobre essa demanda sejam escassos entre publicações, principalmente no que toca aos serviços de APS e da atenção secundária à saúde.…”
Section: Introductionunclassified